2008
DOI: 10.1186/bf03352819
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the upper mantle discontinuities beneath China with teleseismic receiver functions

Abstract: We used teleseismic body waves recorded at stations of the Chinese Center of Digital Seismic Network to map the upper mantle discontinuities beneath continental China. The CRUST2.0 and an S-tomography model beneath each station were combined with the one-dimensional tracing method to convert time series of radial receiver functions to depth series. Clear signatures corresponding to the 410-and 660-km discontinuities ('410' and '660') are visible at almost all of the stations. The average S velocity contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
6
17
0
Order By: Relevance
“…Up to our knowledge, there exists no known mineralogical phase change that would produce the negative signal before P660s. Other studies have also observed similar negative impedance features and have interpreted them as accumulated oceanic crust at the base of the TZ (Eagar et al, 2010;Shen and Blum, 2003;Shen et al, 2008Shen et al, , 2014. This signal is not used in the following analysis, and therefore, we do not further explore its origin.…”
Section: Negative Amplitude Precursory Signalsmentioning
confidence: 68%
“…Up to our knowledge, there exists no known mineralogical phase change that would produce the negative signal before P660s. Other studies have also observed similar negative impedance features and have interpreted them as accumulated oceanic crust at the base of the TZ (Eagar et al, 2010;Shen and Blum, 2003;Shen et al, 2008Shen et al, , 2014. This signal is not used in the following analysis, and therefore, we do not further explore its origin.…”
Section: Negative Amplitude Precursory Signalsmentioning
confidence: 68%
“…9a). The SRFs in each region are stacked and the bootstrap resampling method (Efron and Tibshirani, 1998;Shen et al, 2008) is used to estimate the error of the stacks. Amplitudes exceeding two times of the standard deviation are shaded in color, which gives a 95% confidence detection level.…”
Section: Discussionmentioning
confidence: 99%
“…Li and Yuan (2003) found a 20 km thickened transition zone in northeast China where it is hit by the Pacific slab. Shen et al (2008) and Chen and Ai (2009) Richards and Wicks (1990), Vidale and Benz (1992), Wicks and Richards (1993), Collier and Helffrich (1997), , and Creager (1997, 1998). Shen et al (2008) and Chen and Ai (2009) Richards and Wicks (1990), Vidale and Benz (1992), Wicks and Richards (1993), Collier and Helffrich (1997), , and Creager (1997, 1998).…”
Section: Chinamentioning
confidence: 99%